2014
DOI: 10.1371/journal.pone.0111901
|View full text |Cite
|
Sign up to set email alerts
|

A Biomimetic Collagen Derived Peptide Exhibits Anti-Angiogenic Activity in Triple Negative Breast Cancer

Abstract: We investigated the application of a mimetic 20 amino acid peptide derived from type IV collagen for treatment of breast cancer. We showed that the peptide induced a decrease of proliferation, adhesion, and migration of endothelial and tumor cells in vitro. We also observed an inhibition of triple negative MDA-MB-231 xenograft growth by 75% relative to control when administered intraperitoneally for 27 days at 10 mg/kg. We monitored in vivo the changes in vascular properties throughout the treatment using MRI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 30 publications
2
17
0
Order By: Relevance
“…A common way of measuring proliferation is with BrdU, which living cells incorporate into their DNA and allows them to be counted10. Colorimetric proliferation assays are also common, such as WST-1, cell counting kit-8 assay, which causes the reduction of formazan dye in proportion to the number of living cells and can be measured with a fluorescence plate reader1112. Migration can be measured in real time using an RTCA reader based on electrical impedance13.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A common way of measuring proliferation is with BrdU, which living cells incorporate into their DNA and allows them to be counted10. Colorimetric proliferation assays are also common, such as WST-1, cell counting kit-8 assay, which causes the reduction of formazan dye in proportion to the number of living cells and can be measured with a fluorescence plate reader1112. Migration can be measured in real time using an RTCA reader based on electrical impedance13.…”
mentioning
confidence: 99%
“…Wound healing type assays are also used, where cells are plated with a stopper in the center of the chamber, which is then removed. After a certain number of hours, the cells that have migrated within that region can be counted1112.…”
mentioning
confidence: 99%
“…For example, as mentioned in anti-angiogenesis section, computational biology approaches have enabled identification of cryptic peptide motifs that have strong anti-angiogenic activity as well as biomimetic peptide analogs [177, 294, 295]. Such peptide motifs can be genetically encoded and engineered into a plasmid for delivery singly or in combination with gene delivery nanoparticles.…”
Section: Future Directionsmentioning
confidence: 99%
“…Antiangiogenesis is one of many key methods of cancer therapy, as tumor growth requires robust neovascularization in its microenvironment for increased oxygen and nutrient supply . Lee et al showed that a collagen‐IV derived 20‐mer peptide, that we refer to here as AXT050, inhibits tumor growth in a number of models, including a metastatic tumor model, through its potent antiangiogenic, antilymphangiogenic, and antitumorigenic activities . The naked peptide is also shown to bind to integrin α v β 3 and disrupt integrin‐dependent protein signaling pathways, thereby expanding the arsenal of vascular endothelial growth factor (VEGF)‐independent, antiangiogenesis based cancer therapies .…”
Section: Introductionmentioning
confidence: 99%
“…27 Lee et al showed that a collagen-IV derived 20mer peptide, that we refer to here as AXT050, inhibits tumor growth in a number of models, including a metastatic tumor model, through its potent antiangiogenic, antilymphangiogenic, and antitumorigenic activities. [28][29][30][31] The naked peptide is also shown to bind to integrin a v b 3 and disrupt integrin-dependent protein signaling pathways, thereby expanding the arsenal of vascular endothelial growth factor (VEGF)-independent, antiangiogenesis based cancer therapies. [28][29][30][31] By surface-functionalization and encapsulation of the AXT050 peptide in PLGA-PEG NPs, we hypothesize that targeted NPs with high loading capacity can be fabricated.…”
Section: Introductionmentioning
confidence: 99%